Favorable Response of Pembrolizumab as Second-Line Therapy for Advanced Urothelial Carcinoma with Only Small Lesions to not be Considered Measurable by RECIST - Kadono, Yoshifumi; Kawaguchi, Shohei; Nohara, Takahiro; Shigehara, Kazuyoshi; Izumi, Kouji; Kamijima, Taiki; Seto, Chikashi; Takano, Akinobu; Yotsuyanagi, Satoshi; Nakagawa, Ryunosuke; Miyagi, Tohru; Aoyama, Shuhei; et al. (Urology Journal, 2021)
Purpose: Pembrolizumab is currently considered the standard second-line treatment for advanced urothelial carcinoma (UC). This study aimed to investigate the efficacy and safety of pembrolizumab in patients with advanced UC in real-world data, which is not well-reported. Materials and Methods: The study included 97 patients with advanced UC whose lesions were classified according to the Response Evaluation Criteria in Solid Tumors (RECIST). The median age was 73 years. Nineteen patients (20%) with performance status (PS) 2–4 were included. The percentages of liver, lung, bone, and lymph node metastasis were 18%, 27%, 19%, and 76%, respectively. The efficacy, safety, and risk factors for prognosis were evaluated for patients with and without measurable lesions. Results: The best response was complete response in nine patients (9%) and partial response in 16 patients (17%). The median progression-free survival and overall survival were 3.7 months (95% confidence interval [CI]: 2.8–4.7) and 11.8 months (95% CI: 6.7–17.0), respectively. Twenty-one (22%) patients had no measurable lesions per RECIST. In univariate and multivariate analysis, PS 2–4 and lesions by RECIST were identified as factors associated with short overall survival (OS). The median OS of 18.3 months in patients without lesions by RECIST was significantly longer than the median OS of 6.7 months in patients with lesions by RECIST (p = .012). Conclusion: We demonstrated that good PS 0–1 and no measurable lesions, especially small lesions, by RECIST were favorable prognostic factors in patients with advanced UC treated by pembrolizumab.